2018
DOI: 10.5530/ijper.52.4.81
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Pharmacophore Modeling, Molecular Docking and Virtual Screening Study Reveals 3,5,7-Trihydroxy-2-(3,4,5-trihydroxyphenyl)- 4H-Chromen-4-One as a Potential Anti-Cancer Agent of COT Kinase

Abstract: Background: COT (Tpl2/MAP3K8) is a Serine/ Threonine protein kinase which plays a crucial role in the production of TNF-alpha through the phosphorylation of MEK, ERK pathway and the production of other pro-inflammatory cytokines. Its inhibition has been shown as important to reduce inflammatory diseases and cancer. Material and Methods: Combined Ligand-based and Structure-based pharmacophore model was developed for finding out the potential anticancer agents. These combined pharmacophore model was used as 3D-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…All the ligands generated successful solubility results in the solubility test. The acceptable range for QPlogPC16 is 4.0 -18.0, the acceptable range for QPlogPoct is 8.0 -35.0, the acceptable range for QPlogPw is 4.0 -45.0, the acceptable range for QPlogPo/w is -2.0 -6.5, the acceptable range for QPlogS is -6.5 -0.5, the acceptable range for CIQPlogS is -6.5 -0.5 (Hussain and Verma, 2018 be concluded that bergapten showed the best results in the solubility test, with its best scores among all the selected ligand molecules (Table 08).…”
Section: Discussionmentioning
confidence: 98%
“…All the ligands generated successful solubility results in the solubility test. The acceptable range for QPlogPC16 is 4.0 -18.0, the acceptable range for QPlogPoct is 8.0 -35.0, the acceptable range for QPlogPw is 4.0 -45.0, the acceptable range for QPlogPo/w is -2.0 -6.5, the acceptable range for QPlogS is -6.5 -0.5, the acceptable range for CIQPlogS is -6.5 -0.5 (Hussain and Verma, 2018 be concluded that bergapten showed the best results in the solubility test, with its best scores among all the selected ligand molecules (Table 08).…”
Section: Discussionmentioning
confidence: 98%
“…10. This model can be utilized further for the virtual screening process for finding a similar feature molecule that behaves like a drug 133,134 .…”
Section: Pharmacophore Modeling (Ligand-based)mentioning
confidence: 99%
“…Chromene derivatives have demonstrated antifungal activity in vitro against several kind of pathogenic fungi, such as Cryptococcus neoformans, Torulopsis glabrata, Trichosporon cutaneum, Candida albicans, C. parapsilosis and C. tropicalis [18]. Moreover, there are descriptions in the literature of 4H-chromenes as specific inhibitors of enzymes involved in tumor growth, including topoisomerases I and II [19,20], tubulin [21], caspase [22], COT kinase [23], 17β-dehydrogenase-4 (HSD17B4) [24], telomerase [25], and tyrosinase [26]. However, few reports exist on topoisomerase IB, and no molecular docking studies have yet been carried out, to our knowledge, for 2-amino-3-cyano-4H-chromenes at the active site of this enzyme.…”
Section: Introductionmentioning
confidence: 99%